Primate locomotion linking field and laboratory research - D'Août, Kristiaan; Vereecke, Evie E. (Developments in Primatology: Progress and Prospects, 2011)
Primate locomotion has typically been studied from two points of view. Laboratory-based researchers have focused on aspects like biomechanics and energetics, whereas field-based researchers have focused on (locomotor) behaviour and ecology. Primate Locomotion: Linking Field and Laboratory Research brings together both aspects of primate locomotion studies. Communication between both groups is necessary to identify the specific needs and start up achievable and successful research projects in the field. This volume brings together biomechanists, ecologists, and field-based researchers, who combine both disciplines, and whose contributions facilitate lasting cooperation between the mentioned disciplines and stimulate innovative research in Primatology. The book will be valuable for primatologists, paleo-anthropologists, biomechanists and field biologists, as well as students. About the Editors: Dr. Kristiaan D?Aout is Assistant Professor in the Department of Biology, University of Antwerp, Belgium. Dr. D?Aout is also Research Associate for the Locomorph Project and Coordinator of Biodynamics Research at the Centre for Research and Conservation at the Royal Zoological Society of Antwerp, Belguim. Evie E. Vereecke is part of the Primate Evolution and Morphology Group, School for Biomedical Sciences, University of Liverpool, UK; and Laboratory for Functional Morphology, Department of Biology, University of Antwerp, Belgium.